2018
DOI: 10.3389/fpsyg.2018.00351
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Internal Globus Pallidus Improves Response Initiation and Proactive Inhibition in Patients With Parkinson’s Disease

Abstract: Background: Impulse control disorder is not uncommon in patients with Parkinson’s disease (PD) who are treated with dopamine replacement therapy and subthalamic deep brain stimulation (DBS). Internal globus pallidus (GPi)-DBS is increasingly used, but its role in inhibitory control has rarely been explored. In this study, we evaluated the effect of GPi-DBS on inhibitory control in PD patients.Methods: A stop-signal paradigm was used to test response initiation, proactive inhibition, and reactive inhibition. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…Many researchers have studied DBS in PD patients but only considered behavior, reaction time, symptom cognition, and mood with which to demonstrate therapeutic effect. 7,42 We verified the effect upon neurotransmitters and neural discharge at the level of the neurons. DBS influenced the release of neurotransmitters and spike firing characteristics, in CPU based on the basal ganglia circuit (BG).…”
Section: ■ Discussionmentioning
confidence: 81%
“…Many researchers have studied DBS in PD patients but only considered behavior, reaction time, symptom cognition, and mood with which to demonstrate therapeutic effect. 7,42 We verified the effect upon neurotransmitters and neural discharge at the level of the neurons. DBS influenced the release of neurotransmitters and spike firing characteristics, in CPU based on the basal ganglia circuit (BG).…”
Section: ■ Discussionmentioning
confidence: 81%
“…As a common structure within multiple basal ganglia pathways (direct, indirect, hyperdirect), it is involved in inhibitory control, but has been less studied than STN. Current evidence suggest a positive effect of GPi‐DBS in triggering the action, with no impairment in its suppression (Kohl et al, 2015 ), or even an improvement of the dysfunctional proactive inhibition after turning GPi stimulator ON (Pan et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…, adjustment of the action strategy in advance, according to the environment in which the stop signal will appear) ( Aron, 2011 ; Mirabella, 2021 ). Although Parkinson’s disease (PD) causes obvious motor inhibition defects ( Gauggel, Rieger & Feghoff, 2004 ; Bokura, Yamaguchi & Kobayashi, 2005 ; Antonelli, Ray & Strafella, 2010 ; Wylie et al, 2010 ; Obeso et al, 2011 ; Bloemendaal et al, 2018 ; Pan et al, 2018 ), no consensus has been reached regarding the specific manifestations of these defects in patients with the disease. Some researchers believe that PD is associated with poor proactive and reactive inhibition ( Obeso et al, 2013 ; Jana et al, 2020 ), whereas others found that this defect appears only in reactive inhibition control ( Di Caprio et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%